2018
DOI: 10.1002/14651858.cd013165
|View full text |Cite
|
Sign up to set email alerts
|

Potassium binders for chronic hyperkalaemia in people with chronic kidney disease

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows:To assess the benefits and harms of potassium binders for treating chronic hyperkalaemia among adults and children with CKD.1 Potassium binders for chronic hyperkalaemia in people with chronic kidney disease (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Details of the PICOM questions and associated Cochrane Kidney and Transplant systematic reviews are provided in Table 2. 13,84,148,216,292,[378][379][380][381][382][383] All evidence reviews were conducted in accordance with the Cochrane Handbook, 384 and guideline development adhered to the standards of GRADE (Grading of Recommendation, Assessment, Development, and Evaluation). 385 Literature searches and article selection.…”
Section: Overview Of Processmentioning
confidence: 99%
“…Details of the PICOM questions and associated Cochrane Kidney and Transplant systematic reviews are provided in Table 2. 13,84,148,216,292,[378][379][380][381][382][383] All evidence reviews were conducted in accordance with the Cochrane Handbook, 384 and guideline development adhered to the standards of GRADE (Grading of Recommendation, Assessment, Development, and Evaluation). 385 Literature searches and article selection.…”
Section: Overview Of Processmentioning
confidence: 99%
“…Randomized trials have recently demonstrated efficacy and tolerability of new K-binders agents leading to remarkably lower rates of RAASI discontinuation as compared to traditional anti-hyperkalemic therapy [46,47]. These data call for real-world studies conducted in renal clinics, on large number of patients and with long follow up, to verify effectiveness on hard outcomes [48].…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review of clinical studies evaluating the use of K 1 binders for treatment of chronic hyperkalemia in patients with CKD concluded that the current evidence is insufficient to inform clinical care or policy decision-making in the setting of peritoneal dialysis, hemodialysis, home-based hemodialysis, or transplantation. 3 While there is evidence that hyperkalemia (serum K 1 .5.0 mmol/L) is associated with an increased risk of adverse cardiovascular events in patients receiving maintenance hemodialysis, 38,77 the available evidence base and recommendations on how hyperkalemia should be managed in such patients are very limited. To address the gap in recommendations, this expert consensus statement was developed to provide healthcare professionals with guidance on best practice in serum K 1 monitoring, concomitant prescription of RAAS inhibitors, dietary K 1 restriction, prescription of K 1 binders, and other aspects of managing hyperkalemia in patients receiving maintenance hemodialysis.…”
Section: Overview and Future Directionsmentioning
confidence: 99%
“…While the body of evidence currently available supports the efficacy of SZC and patiromer in managing chronic hyperkalemia, evidence to support their role in the hemodialysis setting is limited. 3 To date, only one RCT has investigated newer K 1 binders in the hemodialysis setting, showing that SZC is efficacious in reducing serum K 1 concentration in patients receiving maintenance hemodialysis. 22 A prospective, randomized, open-label trial is underway to evaluate the efficacy of patiromer to reduce hyperkalemia in patients receiving maintenance hemodialysis (NCT03781089).…”
Section: Gaps In the Evidence Base And Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation